Estudio de factibilidad para la creación de una empresa dedicada a la asesoría contable y tributaria ubicada en el sector norte del distrito metropolitano de Quito - Santafé Salazar, Inés Carolina (2015)
"Feasibility study for the creation of a company dedicated to the accounting and tax consultancy located in the northern part of the Metropolitan District of Quito" This study was developed one time a survey of the needs of individuals and entities engaged in economic activities in the Northern Sector of the Metropolitan District of Quito on issues related to the efficient administration of taxes and accounting policies are made. This project aims to reduce the number of fines and penalties imposed by agencies of control due to lack of timely compliance with the tax and accounting obligations. In order to determine the viability of the project analyzed four key aspects. The first aspect analyzed was the market research, where it was shown that there is sufficient unmet demand for service accounting and tax advice in the area where the business will operate, therefore, there will be acceptance and demand for the service offered. In the technical study we analyzed the operational capacity of the project and the availability of human, technological, material and financial resources to provide counseling service to customers is analyzed, concluding that there is no technical impediment to implement the project. Regarding organizational study could identify the legal formalities to be carried out to establish the company as well as the philosophical and administrative foundation that will serve as a guide for the efficient administration of the business. Finally, the financial study begins with budget analysis of the costs and expenses incurred to develop the project, and an analysis of the expected revenue from the sale of each type of service offered. This study confirms that the project will generate returns for investors during the time period initially established 5 years.